2021
DOI: 10.2196/24973
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Models for Predicting Severe Progression in COVID-19-Infected Patients: Retrospective Study

Abstract: Background Many COVID-19 patients rapidly progress to respiratory failure with a broad range of severities. Identification of high-risk cases is critical for early intervention. Objective The aim of this study is to develop deep learning models that can rapidly identify high-risk COVID-19 patients based on computed tomography (CT) images and clinical data. Methods We analyzed 297 COVID-19 patients from five … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In the correlation heatmap of clinical and laboratory features, CRP and WBC had a strong positive correlation with the endpoint, age was described as significant risk factor related to the endpoint; oxygen saturation and female sex were negatively correlated with the endpoint. This mixed ACNN model obtained a high performance with an AUC of 0.916, accuracy of 93.9% and specificity of 96.9% [102].…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest Ctmentioning
confidence: 87%
“…In the correlation heatmap of clinical and laboratory features, CRP and WBC had a strong positive correlation with the endpoint, age was described as significant risk factor related to the endpoint; oxygen saturation and female sex were negatively correlated with the endpoint. This mixed ACNN model obtained a high performance with an AUC of 0.916, accuracy of 93.9% and specificity of 96.9% [102].…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest Ctmentioning
confidence: 87%
“…In fact, many of the medical imaging studies that integrated heterogenous data have shown that data integration led to AI models with better performance compared to models built with imaging data alone. 53–55 , 62 , 65 , 69 , 76–78 Furthermore, although some data are difficult to get due to privacy issues or simply being unavailable, there are still a range of public data on risk factors that could be easily obtained for modeling. Many studies we reviewed leveraged the “free” data sources, such as the huge amounts of environmental data from the National Oceanic and Atmospheric Administration or the socioeconomic data from the Census Bureau.…”
Section: Discussionmentioning
confidence: 99%
“…They could predict the mortality on days three, five, and seven after hospitalization with an AUC of 0.89, 0.85, and 0.84, respectively. In another AI model by a convolutional neural network (CNN), researchers differentiated the progressive form of infection versus the non-progressive form using CT images and clinical data with an AUC of 0.91 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%